Perineural Invasion is a Strong Prognostic Moderator in Ampulla of Vater Carcinoma: A Meta-analysis. Issue 1 (January 2019) - Luchini, Claudio; Veronese, Nicola; Nottegar, Alessia; Riva, Giulio; Pilati, Camilla; Mafficini, Andrea; Stubbs, Brendon; Simbolo, Michele; Mombello, Aldo; Corbo, Vincenzo; Cheng, Liang; Yachida, Shinichi; et al.
Abstract : Objective: Ampulla of Vater carcinoma (AVC) has a broad spectrum of different prognoses. As such, new moderators of survival are urgently needed. We aimed at clarifying the prognostic role of perineural invasion in AVC. Methods: Using PubMed and SCOPUS databases, we conducted the first systematic review and meta-analysis on this topic. Results: Analyzing 29 articles for a total of 2379 patients, we found that the presence of perineural invasion increased the risk of all-cause mortality more than 2 times (relative risk [RR], 2.07; 95% confidence interval [CI], 1.78–2.42 [ P < 0.0001]; hazard ratio [HR], 2.72; 95% CI, 1.86–3.97 [ P < 0.0001]), of cancer-specific mortality more than 6 times (RR, 6.12; 95% CI, 3.25–11.54 [ P < 0.0001]; HR, 6.59; 95% CI, 2.29–3.49 [ P < 0.0001]), and of recurrence more than 2 times (RR, 2.63; 95% CI, 1.89–3.67 [ P < 0.0001]; HR, 2.54; 95% CI, 1.24–5.21 [ P = 0.01]). Conclusions: Perineural invasion is strongly associated with a poorer prognosis in AVC, influencing both survival and risk of recurrence. It should be reported in the final pathology report and should be taken into account by future oncologic staging systems, identifying a group of AVC with a more malignant biological behavior. Abstract : Supplemental digital content is available in the text.